2006
DOI: 10.1177/0038022920060304
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Gender and Disability in Rural Haryana

Abstract: This paper argues that disability is gendered, culturally constituted and socially negotiated. It explores the nature and form of disability afflicting the individual and social life of women in rural Haryana, in terms of both physical and mental parameters. It describes the community and the family strategies for supporting disabled women in negotiating family, work, economy and society. It also highlights the social effects of physical disability on various stages of their life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Consequently, disabled sexuality is an important area in the discipline of disability studies, more particularly feminist disability studies [7][8][9][10][11]. Even in the Indian context, preliminary work in this domain has been undertaken by feminist researchers in the social sciences [12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…Consequently, disabled sexuality is an important area in the discipline of disability studies, more particularly feminist disability studies [7][8][9][10][11]. Even in the Indian context, preliminary work in this domain has been undertaken by feminist researchers in the social sciences [12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…According to Kalyanpur (), there is a ‘scarcity’ of early intervention programmes and special needs services in rural India. This is the consensus of much of the literature (Mehrotra, ; Azam and Kingdon, ), and highlights the need for more viable educational opportunities. These, as is highlighted through the case study, must be safe, dignified and appropriate.…”
Section: Findings and Discussionmentioning
confidence: 84%
“…From Mehrotra () and Azam and Kingdon's () studies, it is clear that parents play a vital role in the life chances of girls with disabilities. As is often the case, parents cannot afford the time and money needed for appropriate services.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of disability may be considered an existence worse than death in India (Ghai, 2002). Many studies have reported on attitudes towards disability (Dastoor, 1990; Bakheit and Shanmugalingam, 1997; Dalal and Pande, 1999; Paterson et al, 1999; Dalal, 2002, 2006; Thomas and Thomas, 2002; Srivastava and Bajpai, 2005; Mehrotra, 2006); common views may include: charitable, bad karma, external locus of control, visible disabilities less acceptable, inferior or incompetent, cure driven and family duty to care. The Indian milieu offers little understanding of the social model of disability, which locates the problem at the level of the society (Ghai, 2002).…”
Section: Disability and Rehabilitation In Indiamentioning
confidence: 99%